Evaluation of lateral throat form-an in vivo study - Rastogi, Isha (Journal of Oral and Dental Sciences, 2014)
Introduction: Lateral throat form is an area situated at the distal end of the alveololingual sulcus. Its synonyms are distolingual vestibule and retromylohyoid fossa. The extension of denture into this area can resist horizontal forces, increase border sealing, prevent the tongue from returning to its polished surface, act as a displacing lever on the denture border and contribute to neuromuscular control. Purpose: To evaluate the relative proportion of the lateral throat forms in 74 patients aged between 18-45 years from Lucknow(Eastern UP).A designed instrument was used to confirm LTF. Method: LTF was intraorally evaluated by finger method and instrument.Then the mandibular impressions were made and casts obtained for measurements in this study. Results: The data obtained was subjected to statistical analysis.It was seen that majority of  the lateral throat forms among the patients were class I, followed by class II and class III were rare.Extension of denture border in the distolingual region (vertically and horizontally) was found to be more in class I lateral throat form compared to class II and least for class III.Significant differences were observed between the vertical dimension in patients’ mouth to that of their diagnostic casts.Vertical and horizontal dimensions correspond to each other.The lateral throat form needs to be measured, to select proper stock tray for primary impression.The custom tray has to be adjusted and extended properly to record lateral throat form with more accuracy. Conclusion: It is concluded that lateral throat form has to be properly recorded for mandibular denture stability and for its successful fabrication.   Keywords: Lateral Throat Form (LTF), Dentilingual Vestibule, Retromylohyoid Fossa, Alveolingual Sulcus, Lingual Border Anatomy.